UJI AKTIVITAS MOISTURIZER PROBIOTIK PRODUK KECANTIKAN TERHADAP BAKTERI Propionibacterium acnes dan Staphylococcus epidermidis - Nina Irmayanti Harahap; elysa elysa; nurul dahlia harahap (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2026)
Acne is one of the most common skin disorders affecting adolescents and young adults, with severity ranging from mild to severe. The pathogenesis of acne is influenced by multiple factors, including the presence of skin microbiota, particularly Propionibacterium acnes and Staphylococcus epidermidis. Objective: This study aims to evaluate the effectiveness of probiotics formulated in a moisturizer gel in inhibiting bacterial activity without compromising their moisturizing function. Methods: This study employed an experimental design to evaluate the antibacterial activity of moisturizer gel formulations using the well diffusion method, with inhibition zone diameter as the measured parameter. Additionally, a moisturizing test was conducted on 18 volunteers with dry skin conditions. Results: The results demonstrated that all moisturizer gel formulations exhibited moderate antibacterial activity, with inhibition zone diameters ranging from 5 to 10 mm. The moisturizing test conducted on 18 volunteers indicated that all formulations maintained skin moisture within the normal range, with values between 30% and 50%. Conclusion: Based on the antibacterial activity test, it can be concluded that probiotic-containing moisturizer gels exhibit antibacterial properties. However, their effectiveness remains moderate, as indicated by the inhibition zone diameters within the range of 5–10 mm.